In vitro and In silico Studies of Multimodal Gd-free diagnostic/Theranostic Agents; Synthesis, Photophysical Characterization, Relaxometric Analysis, Virtual Screening, and Validation - Sathiyajith , CuhaWijay; Hallett , Andrew J.; Edwards , Peter G. (Novel Aspects on Chemistry and Biochemistry Vol. 5, 2023)
This chapter demonstrates the successful preparation and analytical and spectroscopic characterization of three new EDTA-N, N'' Bis(amides) ligands functionalized by luminophores (4-(aminomethyl)pyridine (L1) and 2-aminoanthraquinone (L2) and sulphonate (aminomethanesulfonic acid (L3)) on the amide side-arms (L1-L3) and their transition metal complexes (Mn (II), Cu (II) (except for L3), Zn (II)). Harnessing the strengths of two or more imaging modalities in terms of spatial resolution (for MRI) and specificity (for PET/OI) in a small molecule could immensely facilitate multimodal theranostic. A theranostic agent as a hybrid small molecule comprising both diagnostic and therapeutic arms with enhanced stability could effectively deliver the promise of precision medicine. Also, this cannot be achieved by a mere combination of two imaging agents unless they have identical pharmacodynamic properties. On the other hand, toxicity issues also pose limitations. The potential of L1-L3 to act as a dual-modal contrast agent for magnetic resonance imaging (MRI CA) was evaluated by measuring physicochemical properties such as (a) thermodynamic stability by measuring macroscopic protonation constants and stability constants with potentiometric titrations (b) R1 relaxivities by NMR relaxivity studies (c) spectrophotometric investigations. The stability of the AURKB-L1 complex was evaluated by monitoring the root-mean-square deviation (RMSD) of the protein C\(α\) atoms and the root-mean-square fluctuation (RMSF) of the amino acid residues as well as the inhibitor-protein hydrogen bonding interactions along the simulation trajectory. Comparative studies revealed Mn-L1 has a performance comparable to the commercially available gadolinium-based contrast agents and is relatively higher than TESLASCAN. The photophysical characterization confirmed the ability of L1 and L2 to act as on-off type, fluorescent-based chemosensors for Cu (II). Time-resolved fluorescence investigations (TCSPC) indicated the potentiality of L1 for live-cell imaging. A structure-based virtual screening followed by molecular dynamic simulation validated that the potential of L1 could act as a multi-target ligand to modulate the activity of two unrelated receptor proteins: Aurora kinase B and human serum albumin.